Allergen characteristics, quality, major allergen content and galenics for mite allergen-specific immunotherapy preparations - Brehler, Randolf; Klimek, Ludger (Allergo journal international, 2023)
Summary House dust mite extracts for allergen-specific immunotherapy (AIT) require in Germany as other common allergens (pollen from sweet grasses [except maize], birch, alder, hazel; bee and wasp venom) marketing authorisation according to the German Therapy Allergen Ordinance (“Therapieallergene-Verordnung”, [TAV]). Mite allergen extracts that have been approved and also those which are in the approval process are subject to government batch testing. Batch test passing is a prerequisite for marketability. Appropriate quality, efficacy, and safety are prerequisites for the approval of house dust mite extracts. Five HDM allergen extracts from four manufacturers are currently approved in Germany for subcutaneous or sublingual therapy; further extracts are in the approval process. The allergen strength of different products is not comparable; manufacturers use company-specific units to describe the strength. Of the three known major allergens (Group 1 allergens: Der p 1, Der f 1, Group 2 allergens: Der p 2, Der f 2 and Group 23: Der p 23, Der f 23) only Group 1 and Group 2 allergens are usually used to standardize the extracts. Group 23 allergens are localized in the outer membrane of mite faeces, and elution requires special extraction methods. To be efficacious in a single patient an allergen extracts used for AIT must contain all allergen components against which the patient is sensitised. Based on post hoc analyses of large clinical studies, it has been proven for house dust mite tablets that Der p 23 is also contained. In Germany, the Paul Ehrlich Institute is responsible for the approval of therapeutic allergens. For the marketing authorisation information on production procedures, and quality are necessary efficacy and safety (positive benefit risk ratio) of the product must be demonstrated in clinical trials according to the current state of the art.